Clinical, microbiological, and immunological studies in patients with immunoglobulin deficiencies and gastrointestinal disorders. Issue 6 (June 1972) - Brown, W. R.; Butterfield, D.; Savage, D.; Tada, T.
Abstract : Seven patients with gastrointestinal disorders and deficiencies of serum and secretory immunoglobulins were evaluated clinically, microbiologically, and immunologically. Five patients had generalized deficiencies of immunoglobulins; two were selectively deficient. Diarrhoea and malabsorption in six of the seven patients were at least partially explained. Four of the five patients with generalized hypogammaglobulinaemia had intestinal infestation with Giardia lamblia ; in three of the five, excessive numbers of anaerobic bacteria were cultured from small bowel fluids. Despite much variability in relative severity of patients' respiratory and gastrointestinal tract symptoms, deficiencies of mucosal immunocytes and immunoglobulins in nasopharyngeal and gastrointestinal tract tissues and secretions were similar. Except for one selectively IgA-deficient patient, all patients were deficient in IgE. The study characterizes in greater detail than heretofore the gastrointestinal disorders associated with immunoglobulin deficiency states.